Pengaruh literasi keuangan dan perilaku menabung terhadap kesiapan pensiun pada pekerja di Kota Timika - Pratama, Adhi; Srimindarti, Ceacili; Hendrian (AKUNTANSI DEWANTARA, 2023)
Workers need to prepare provisions in order to have readiness to undergo retirement. The retirement provisions in question include financial literacy and saving behavior, both of which can be a solution to dealing with financial needs in retirement. This study aims to determine the effect of financial literacy and saving behavior on retirement readiness. The object of this research is active workers who work and are in the Timika City area. The approach used is quantitative, the type of data used in this study is primary data which is the respondent's answer through a questionnaire distributed using google form. The number of samples in this study were 100 respondents with an age range between 20-40 years. The scale used in measuring variables is a Likert scale. Data analysis using the PLS (Partial Least Square) method processed with Smart PLS 3.0 software. The results obtained in this study indicate that financial literacy and saving behavior have a significant positive effect on retirement readiness. In this study, the proposed model can explain retirement readiness with a percentage of 54.7%, while the rest is explained by other variables outside this study